The Role of Board Gender Diversity In Moderating The Effect of Corporate Governance on Earnings Management (A study of companies listed on the Jakarta Islamic Index 70 from 2020 to 2023) - Muhamad Yusuf Firdaus; Ahmad Mifdlol Muthohar; Rakotoarisoa Maminiaina Heritiana Sedera (Islamic Accounting Journal, 2025)
Objective & object: This study aims to analyze the effect of corporate governance, proxied by independent commissioners, audit committees, managerial ownership, and institutional ownership, on earnings management, with board gender diversity as a moderating variable. Methods: The population in this study was companies listed on the Jakarta Islamix Index 70 for the period 2020-2023. The sample in this study consisted of 24 companies. This study used quantitative methods. The data used in this study was secondary data in the form of annual reports from the 24 companies in the sample. The analysis tool used in this study was the Eviews 12 application. Results & Conclusions: The results of the study indicate that independent commissioners, audit committees, managerial ownership, and institutional ownership have no effect on earnings management. However, board gender diversity has a negative effect on earnings management. Furthermore, the board gender diversity variable is unable to moderate the effect of independent commissioners, managerial ownership, and institutional ownership on earnings management, but it successfully moderates the effect of the audit committee on earnings management. Limitations: The selection of independent variables and moderating variables was inappropriate because the results of the study showed that only 2 of the 9 hypotheses were accepted. This occurred because the selection of operational definitions and measurements for each variable was inaccurate. Implications: This study can provide a reference for companies to consider the elements that influence profit management, so that they can make the right investment decisions.